Pendampingan Santri Kreatif melalui Panggung Kreasi Seni di Pondok Pesantren Hidayatul Mubtadi’in Wedi Kapas Bojonegoro - Moh. Sa'diyin; A. Imam Syamsudin; Hikmatun Nadhifah; Khusnul Khotimah; Moh. hafidh Nasruddin; Putri Diyah Safitri (Santri: Journal of Student Engagement, 2022)
Realizing your potential is very important. Thus, this assistance is carried out in an effort to make the potential contained in PP Hidayatul Mubtadi'in students more optimal. This assistance is manifested in the form of talent development training, the target of this assistance is all students, so that their potential can have a positive impact on developing students' talents and developing the quality of Islamic boarding schools. This asset empowerment assistance is carried out using the ABCD (Asset Base Community Development) approach with three stages, namely: Inculturation; Discovery; Dreams; Design; Define; and Destiny. The steps taken in mentoring creative students through the art creation stage, namely: training activities for students' talent development. This activity begins with the initial activity, the second activity, and the final activity. With this training program, students will realize their potential and are always motivated to innovate more by taking advantage of the opportunities and talents they have, therefore their potential is increasingly attached to them and the Islamic boarding school is increasing for a more prosperous future.